Rational modules and higher order Cauchy transforms - James Li-Ming Wang (International Journal of Mathematics and Mathematical Sciences)
We apply the higher order Cauchy transforms to describe the closures of rational modules with respect to the LP norms, the uniform norm and different Lipschitz norms on a compact set in the plane.